Macrozoobenthos of Shamkirchay river under new environmental circumstances (Republic of Azerbaijan) - Aliyev, Saleh; Farzali, Shabnam (Arak Univ, Arak, 2022)
Shamkirchay is one of the transboundary rivers of Azerbaijan and one of the main right tributaries of the Kura River, the main water body. For the first time, from November 2018 to March 2020, macrozoobenthos, an important component of the river's hydrofauna, were studied comprehensively, depending on the seasons. During the study, 91 species of macrobenthic organisms were identified, the development of which varied between 19-91 species, depending on the season. At the same time, we have set some hydrochemical indicators. The status of the river and its distribution on saprobic organisms and their biocenoses were also investigated during the observations.
Keywords: Biocenosis; biomass; macrozoobenthos; saprobity; Shamkirchay